Superchervʹi͡ak - Donaldson, Julia (Chytarium, 2023)
Superworm's bug friends attempt to free him from the clutches of Wizard Lizard who, having heard of Superworm's wondrous and heroic deeds, captures him and forces him to dig for treasure.